2015
DOI: 10.1038/gim.2014.185
|View full text |Cite
|
Sign up to set email alerts
|

A preliminary investigation of genetic counselors’ information needs when receiving a variant of uncertain significance result: a mixed methods study

Abstract: PurposeTo explore genetic counselors’ information preferences on reports of variant of uncertain significance (VUS) results from cancer genetic testing.MethodsThis mixed methods report (quantitative and qualitative approaches) utilized a survey of genetic counselors containing closed- and open-ended questions to explore genetic counselors’ information needs and perceptions of the industry’s current information sharing practices. Descriptive statistics were calculated for responses to the closed-ended questions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 22 publications
2
27
0
Order By: Relevance
“…In a recent survey exploring genetic counsellors' information preferences on VUS laboratory reports, a minority of respondents expressed concerns about awareness of VUS and appropriate medical recommendations among other health-care professionals. 69 The survey also highlighted that the majority of respondents (243/267 (91%)) reported too little information provided on laboratory VUS reports, and that additional information would help contextualise the VUS result for patients. This is supported by a previous survey of breast cancer genetic counselling practices, where only 63% of genetic counsellors felt their patients understood the meaning of a VUS finding.…”
Section: Interpreting Brca Test Results: Dealing With Variants Of Unkmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent survey exploring genetic counsellors' information preferences on VUS laboratory reports, a minority of respondents expressed concerns about awareness of VUS and appropriate medical recommendations among other health-care professionals. 69 The survey also highlighted that the majority of respondents (243/267 (91%)) reported too little information provided on laboratory VUS reports, and that additional information would help contextualise the VUS result for patients. This is supported by a previous survey of breast cancer genetic counselling practices, where only 63% of genetic counsellors felt their patients understood the meaning of a VUS finding.…”
Section: Interpreting Brca Test Results: Dealing With Variants Of Unkmentioning
confidence: 99%
“…70 It should be noted however, that a minority of genetic counsellors believe interpretation of additional information to guide patient medical management could be problematic, as interpretation was the responsibility of the laboratory conducting the test. 69 …”
Section: Interpreting Brca Test Results: Dealing With Variants Of Unkmentioning
confidence: 99%
“…These studies serve as the groundwork to inform the design of software tools [17,18]. While most of these studies have focused on genetic counselors' information needs, some findings may be generalized to other clinicians.…”
Section: Introductionmentioning
confidence: 99%
“…Genetic counselors have expertise when reviewing GS reports; therefore, information that they deem necessary should be emphasized when non-genetic expert clinicians are reviewing GS reports. For example, a study surveying genetic counselors showed that there is a perceived lack of information on the classification system for variants of unknown significance (VUS) included in laboratory reports, highlighting a need for improved GS reports to provide transparency [18]. That study also found that genetic counselors wanted more information, such as patient information, in reports to help contextualize VUS results [18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation